Evaluation of Validity and Reliability Using Rasch Model and SPSS on Students' Mathematical Creative Thinking Ability - Febryana, Ultami Ismayani; Rahmania, Fadhilah; Faradillah, Ayu; Jusra, Hella (Pattimura Proceeding, 2024)
Mathematical creative thinking is an important skill for students to face global challenges and advances in science and technology. However, previous research shows that this skill is still low among Indonesian students. Accurate measurement can be ensured by valid and reliable instruments. The purpose of this study is to evaluate the validity and reliability of the mathematical creative thinking ability test instrument using the Rasch Model and SPSS. The research method is quantitative with a survey approach, involving 106 participants from various demographic backgrounds. The results of the validity test using the Rasch model showed that the eight items on the mathematical creative thinking ability test instrument met the criteria with the ideal value range for Outfit MNSQ, Outfit ZSTD, and PTMEA-CORR. In addition, the validity test results using SPSS show that the eight items have a correlation coefficient value that exceeds the r product moment value. The results of the analysis showed that the instruments tested were valid and reliable with a Cronbach's Alpha value of 0.73 using the Rasch Model and SPSS. However, the Rasch Model showed 24 persons that did not fit, which means that the Rasch model's ability to provide more specific results. Both methods can be used effectively to measure the validity and reliability of mathematical creative thinking test instruments and the Rasch Model provides more detailed information in identifying persons who do not fit